IDENTIFICATION, CHARACTERIZATION AND VOLUMETRIC ESTIMATION OF DELTAIC RESERVOIR ON LOWER MAIN ZONE UTARI GAS FIELD, KUTAI BASIN, EAST KALIMANTAN - Noor Radhityatama, Fachreza
Kutai Basin is one of the largest hydrocarbon producing basin in Indonesia, with an estimated area of around 60.000 km2 and filled with Tertiary sedimentary deposit around 14 km thick. Utari field is one of the fields located on Kutai Basin, and is the biggest gas field in Indonesia. It is located on the median axis of the Mahakam Delta. Utari Field has an anticline axis trending NE-SW, which forms a structural and stratigraphic trap for this field petroleum system. Generally, reservoirs on this field is found as deltaic deposit such as channels and bars. The aim of this study is to go beyond normal targets and identify reservoir on the Lower Main Zone (N15-N14) which is located on the lower part of the deltaic petroleum system as an advanced exploration effort on the Utari Field. This exploration is done by using seismic data and exploration wells on the Central and North-West area. The result of geometry identification using seismic amplitude shows that there are 2 types of sedimentary bodies on this study area, which are distributary channels and mouth bars. Based on analysis of exploration well data, it is known that there is a potential mature source rock (Tmax ~440o & VR ~0,9%) consisting of a mixed type II kerogen and type III kerogen. Furthermore, a depth map is made on the research area which is then correlated to the depth of source rock maturity so that the potential kitchen of this reservoir are can be estimated. Based on the analysis, it is found that the potential kitchen area of this reservoir is located on the eastern area of Utari Field, so the reservoir can be charged from the syncline on this area, with an estimated fluid in form of wet gas. To estimate the volumetric of this reservoir, a reservoir characteristic analogue is analyzed based from the reservoirs of an exploration well located on a bar facies. This marginal levee analogue shows several characteristics ( ? =0.085 & Sw=0.86), which can be used to assume the characteristics on the channel itself ( ? =0.12 & Sw=0.42). Finally, these characteristics are used to calculate the volumetric estimation of the reservoir, with the biggest reservoir containing approximately 12.98 BCF of initial gas in place.